Two thousand–year reconstruction of livestock production intensity in France using sediment-archived fecal Bacteroidales and source-specific mitochondrial markers. (September 2015) - Etienne, David; Destas, Mathilde; Lyautey, Emilie; Marti, Romain; Ruffaldi, Pascale; Georges-Leroy, Murielle; Dambrine, Etienne; Topp, Edward
The reconstruction of past pastoral activities based on microscopic methods (pollen and coprophilous fungal ascospores) does not accurately identify the domestic species involved. In contrast, source-specific DNA markers, commonly employed in water quality microbial source tracking (MST) studies, may represent a promising tool for retrospectively identifying species-specific fecal contamination in sediment deposition. In the present study, molecular methods were used to quantify Bacteroidales and identify ovine and bovine mitochondrial DNA extracted from sediment cores from two forest hollows comprising 2000 years of deposition. The DNA marker abundance was contrasted with the abundance of ascospores and plant-specific pollen throughout the sediment chronosequence. The distribution of DNA markers indicated an agro-pastoral practice transition from pasture/crop production to forested landscape from the second Iron Age/classical Antiquity to the end of the Roman period/modernity, in correlation with microscopic markers. During the second Iron Age/classical Antiquity, hollows were likely used to water herds, whereas during the late Antiquity, low Bacteroidales abundances and the sporadic detection of bovine and ovine DNA markers confirm the progressive afforestation observed using pollen data. For the end of the Roman period and modern times, reforested areas are characterized by the absence of ovine and bovine DNA markers while low Bacteroidales abundances suggest the presence of wild herbivores. The present study has established that in tandem with microscopic methods, sediment-archived fecal-specific bacterial and mitochondrial DNA are extremely useful for reconstructing agricultural practice over timeframes of millennia.